The official five star fitness boot camp workout - Flach, Andrew (Hatherleigh/Five Star Fitness, 1999)
From coast to coast Boot Camp classes have become big at fitness centers. Men, and especially women, are attracted to the "no frills" and high energy approach of this military style workout. In the summer of 1998, the Five Star Fitness team sponsored a series of fitness classes in the resort town of East Hampton, New York, called the Five Star Fitness Boot Camp. The Official Five Star Fitness Boot Camp Workout shows readers how to build a strong foundation for lifelong fitness. It is written for men and women, and the workouts can be performed by a wide range of fitness levels. Detailed, progressive 6-week workout plans for beginner, intermediate, and advanced workout warriors are featured. Additional sections include: stretching and flexibility, weight training, field exercises, boxing, and calisthenics. Based upon the fitness sensation of Summer 1998, this book captures the spirit of the Boot Camp craze with style and verve.